Diagnostic Accuracy of the RIPASA and Alvarado Scores in Screening for Acute Appendicitis: A Histopathology-Based Retrospective Validation Study - Muhammad Azmi Fanany; Elvita Nora Susana; Malahayati Rusli Bintang (Universitas Muhamadiyah Manado, 2026)
Background: Acute appendicitis is the most common abdominal surgical emergency, yet its diagnosis remains a clinical dilemma owing to frequently atypical presentations. Clinical scoring systems were developed to expedite and improve diagnostic accuracy. This study aimed to compare the diagnostic accuracy of the RIPASA and Alvarado scores against histopathology as the gold standard. Methods: A retrospective cross-sectional analytic study of 125 patients with suspected acute appendicitis who underwent appendectomy at Hj. Bunda Halimah Hospital, Batam, between 1 January 2022 and 31 December 2024. The Alvarado (cut-off ≥7) and RIPASA (cut-off ≥7.5) scores were derived from medical records and compared with histopathology. Sensitivity, specificity, positive (PPV) and negative (NPV) predictive values, accuracy, and the area under the curve (AUC) were analysed. Results: Histopathology confirmed appendicitis in 114 of 125 patients (91.2%; negative appendectomy rate 8.8%). The Alvarado score yielded a sensitivity of 87.7%, specificity 63.6%, PPV 96.1%, NPV 33.3%, and accuracy 85.6% (AUC 0.797; 95%CI 0.715–0.863). The RIPASA score yielded a sensitivity of 91.2%, specificity 54.5%, PPV 95.4%, NPV 37.5%, and accuracy 88.0% (AUC 0.847; 95%CI 0.772–0.905). Conclusion: Both scores demonstrated good and comparable discriminative capacity; RIPASA tended to be more sensitive and marginally more accurate, whereas Alvarado was more specific. The overlapping AUC confidence intervals preclude a conclusion of statistically significant superiority of RIPASA. Both instruments are suitable screening tools in resource-limited, imaging-scarce settings.